Drip irrigation - an efficient system of water use - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
A farmer explains his system of using drip irrigation with harvested rainwater to grow vegetable crops